Increased remineralization of tooth enamel by milk containing added casein phosphopeptide-amorphous calcium phosphate - Walker, Glenn; Cai, Fan; Shen, Peiyan; Reynolds, Coralie; Ward, Brent; Fone, Christopher; Honda, Shuji; Koganei, Megumi; Oda, Munehiro; Reynolds, Eric (Journal of dairy research, 2006)
Casein phosphopeptide amorphous calcium phosphate nanocomplexes (CPP-ACP) in chewing gum, lozenges and mouthrinses have been shown to remineralize enamel subsurface lesions in human in situ experiments. The aim of this double-blind, randomized clinical study was to investigate the capacity of CPP-ACP added to bovine milk to remineralize enamel subsurface lesions in situ. Ten subjects drank milk containing either 2·0 or 5·0 g CPP-ACP/l or a control milk whilst wearing removable appliances with enamel slabs containing subsurface demineralized lesions. Each 200 ml milk sample was consumed once a day for each weekday over three consecutive weeks. After each treatment and one weeks rest the subjects crossed over to the other treatments. At the completion of the treatments the enamel slabs were removed and remineralization determined using microradiography and microdensitometry. The results demonstrated that all three milk samples remineralized enamel subsurface lesions. However, the milk samples containing CPP-ACP produced significantly greater remineralization than the control milk. The remineralising effect of CPP-ACP in milk was dose-dependent with 2·0 and 5·0 g CPP-ACP/l producing an increase in mineral content of 70 and 148%, respectively, relative to the control milk. The differences in remineralization following exposure to the three milk samples were all statistically significant (P<0·001). In conclusion, this study shows that the addition of 2·0–5·0 g CPP-ACP/l to milk substantially increases its ability to remineralize enamel subsurface lesions.